Epistasis in the expression of relevant traits in cassava (Manihot esculenta Crantz) for subhumid conditions - Catch, NT; Pérez Velásquez, Juan Carlos; Lenis Calderon, Jorge Iván; Calle, F.; Morante, N; Ceballos, H. (Oxford University Press, 2005)
There is limited knowledge on the inheritance of agronomic traits in cassava and the importance of epistasis for most crops. A nine-parent diallel study was conducted in subhumid environments. Thirty clones were obtained from each F1 cross. Each clone was represented by six plants, which were distributed in three replications at two locations. Therefore the same 30 genotypes of each F1 cross were planted in the three replications at the two locations. Analysis of variance suggested significant genetic effects for all variables analyzed (reaction to thrips, fresh root and foliage yields, harvest index, dry matter content, and root dry matter yield). Significant epistatic effects were observed for all variables, except harvest index. Dominance variance was always significant, except for dry matter content and dry matter yield. Additive variance was significant only for reaction to thrips. Results suggested that dominance plays an important role in complex traits such as root yield. The significance of epistasis can help us understand the difficulties of quantitative genetics models and QTLs in satisfactorily explaining phenotypic variation in traits with complex inheritance. Significant epistasis would justify the production of inbred parental lines to fix favorable allele combinations in the production of hybrid cassava cultivars.